The Effect of Incentives and Work Environment Through Job Satisfaction on Employee Performance at The Jambi Bank of Regional Development Bangko Branch Office - Kurniawan, Muhammad Dhani; Zahari, M.; Sudirman, Sudirman (Dinasti Publisher, 2026)
The effectiveness of banking organizations in the face of competition and rising service demands is largely dependent on employee performance. The purpose of this study is to assess how incentives and the workplace affect job satisfaction, how job satisfaction affects performance, how incentives and the workplace affect performance, and how incentives and the workplace influence employee performance through job satisfaction. The Jambi Bank of Regional Development's Bangko Branch Office served as the site of this study. This study included both principal and supplemental data. There were 57 responders in the study sample. Saturated sampling was the method utilized. Both quantitative and descriptive analysis were used in this investigation. Path study using the Partial Least Square (PLS) method was employed in the quantitative study. Software called SmartPLS 3.0 helped with data processing. The findings demonstrated that job satisfaction was positively and significantly impacted by rewards and the workplace. Employee performance was positively and significantly impacted by incentives and the work environment. Employee performance was significantly impacted by job satisfaction, while employee performance was not significantly impacted by job satisfaction incentives. ASN performance was significantly and favorably impacted by motivation. At the Jambi Bank of Regional Development's Bangko Branch Office, employee performance was positively and significantly impacted by the work environment through job satisfaction. These results highlight how crucial equitable reward programs and a positive workplace are to raising bank employee satisfaction and productivity.